STUDY EFEKTIVITAS KEBIJAKAN INOVASI DOKADU (DOKUMENTASI PENGADUAN) DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KOTA MAGELANG - Kumalasari, Reta (Jendela Inovasi Daerah, 2023)
Management of public service complaints is an important part of improving the quality of services provided by the government to the community. The reasons for the importance of complaints include: 1) the public has the right to obtain quality, non-discriminatory public services in accordance with established standards, 2) public complaints are an opportunity for government agencies to evaluate and improve, 3) as government media in providing response to public complaints. To improve services, one of them is by making an innovative breakthrough that makes it easier for the complaints team to resolve problems with public complaints. This innovation is called DOKADU (Complaint Documentation). This study aims to analyze the effectiveness of the DOKADU (Complaint Documentation) innovation policy in resolving public complaints at the Population and Civil Registration Office of Magelang Municipality for a period of 5 years (2017 – 2021). This research uses descriptive qualitative narrative method. The results of the study show that since the implementation of innovations over the last 5 years (2017 – 2021) it shows that there is a tendency for the number of complaints that have been received and handled successfully to increase (99.85%). FAQs (Frequently Asked Questions) that are frequently complained about can be monitored because segmentation/category of complaints can be carried out and ownership of population administration documents increases. This shows that the quality of handling public complaints at the Disdukcapil in Magelang Municipality has increased. This innovation needs to be continuously improved and developed so that it becomes a smart book for the public complaints team. In the future, it is hoped that there will be a software application that assists in documenting complaints, so that population administration services in Magelang Municipality will make the people happier according to the Vision of “Magelang Municipality, namely Magelang is Healthy, Advanced and Happy ".